2012
DOI: 10.1177/2151458512454878
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Osteoporosis in High-Risk Patients Prior to Hip Fracture

Abstract: Purpose: Hip fractures in older adults are common and serious events. Patients who sustain fragility hip fractures are defined as having osteoporosis. Patients with dementia or a history of a prior fragility fracture are at increased risk of a future fracture. This study assesses prefracture osteoporosis diagnosis and treatment in high-risk groups. Methods: A case-control analysis of a database of all patients age !60 years admitted for surgical repair of nonpathological, low-impact femur fracture between May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
1
15
0
2
Order By: Relevance
“…The initiation rate in this study was higher when compared with studies examining the prefracture osteoporosis treatment rate among those patients presenting with a fracture. These rates ranged from 8% to 17% . Even after fractures, patients reported in the literature tend to have low osteoporosis treatment initiation rates, ranging primarily from 8% to 24% .…”
Section: Discussionmentioning
confidence: 99%
“…The initiation rate in this study was higher when compared with studies examining the prefracture osteoporosis treatment rate among those patients presenting with a fracture. These rates ranged from 8% to 17% . Even after fractures, patients reported in the literature tend to have low osteoporosis treatment initiation rates, ranging primarily from 8% to 24% .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that non-treatment of osteoporosis is common [8][9][10][11][12][13][14][15][16][17][18][19][20] , whether assessed after clinical or self-reported OP diagnosis 10,20 , before OP-related fractures 8,11,16 , or after fractures 9,[11][12][13][14][15][16][17][18][19] . Common barriers to treatment initiation include: concerns over side effects 21 including gastro-intestinal (GI) events [22][23][24][25] , cost 26 , and patient frailty 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Common barriers to treatment initiation include: concerns over side effects 21 including gastro-intestinal (GI) events [22][23][24][25] , cost 26 , and patient frailty 26 . While some previous studies have attempted to identify characteristics associated with the likelihood of OP treatment [8][9][10]19 , most published studies have focused on treatment among patients newly indicated for treatment and did not include patients with prior use of therapy, even though prior osteoporosis therapy has been shown to be predictive of future treatment 27 . Additionally, few studies of OP nontreatment focus on a Medicare population.…”
Section: Introductionmentioning
confidence: 99%
“…Algunos estudios han demostrado la asociación entre la pérdida de densidad mineral ósea y el deterioro cognitivo (514)(515)(516) , así como con la EA (517)(518)(519)(520)(521) . Los enfermos de…”
Section: Densidad Mineral óSea Y Enfermedad De Alzheimerunclassified
“…Son muchos los autores que enfocan sus investigaciones hacia la comorbilidad entre la EA (517)(518)(519)(520)(521) y otras demencias (514)(515)(516) con la osteoporosis, o pérdida de densidad mineral ósea. Aunque no son tantos los que evalúan al eficacia de algún tipo de intervención.…”
Section: Densidad Mineral óSeaunclassified